Analisis Jamu sebagai Pengalaman Wisata di Samabe Suites and Villas, Bali - Haliza Arsyadila Nurdin; Dally Nur Arif; Irena Novarlia (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
Jamu is a traditional drink made by Indonesian people which comes from natural ingredients, like plant parts such as rhizomes, leaves, bark and others. Samabe Suites and Villas is one of the five star accommodations in Bali which has a jamu menu in their main bar. This research aims to analyze the potential of jamu as a tourism experience at Samabe Suites and Villas, Bali. The method used in this research is the qualitative phenomenological method. Data collection methods through interviews, observation and secondary data from related journals. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation and conclusions. The research results show that herbal medicine has great potential in the context of cultural inheritance through tourism experiences at the luxury accommodation Samabe Suites and Villas, Bali. With its luxury, uniqueness and specialty, jamu will leave memorable memories for tourists.   Keywords: Cultur, Jamu, Tourism Experience